2018
DOI: 10.1111/jhn.12600
|View full text |Cite
|
Sign up to set email alerts
|

Dietetics students’ experiences of dietetics workforce preparation and preparedness: a systematic review and qualitative synthesis

Abstract: Background: Dietetics students are a widely researched group. As emerging dietitians, they can provide valuable insights to inform how dietetics education programmes may be enhanced to meet contemporary healthcare needs. This review aimed to systematically synthesise dietetics students' experiences of dietetics workforce preparation. Methods: MEDLINE, CINAHL, Embase, PsycINFO, ERIC, Informit and ProQuest Dissertations and Theses Global were searched to identify research published until June 2017. Studies inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 77 publications
1
12
0
Order By: Relevance
“…While data on dietetics graduate outcomes in Australia is lacking (Morgan et al 2019c), this strong competition for obvious job opportunities as a result of a perceived graduate oversupply has been confirmed by dietetics educators in both academic and practice settings (Morgan et al 2018(Morgan et al , 2019b. These findings support the need to address the competitive landscape resulting from supply/demand mismatches that exist within dietetics internationally (Nyland and Lafferty 2012;Ruhl and Lordly 2017;Morgan et al 2019a). Providing students with experiences across diverse practice contexts to illustrate the breadth of possible careers is one potential strategy.…”
Section: Discussionmentioning
confidence: 89%
“…While data on dietetics graduate outcomes in Australia is lacking (Morgan et al 2019c), this strong competition for obvious job opportunities as a result of a perceived graduate oversupply has been confirmed by dietetics educators in both academic and practice settings (Morgan et al 2018(Morgan et al , 2019b. These findings support the need to address the competitive landscape resulting from supply/demand mismatches that exist within dietetics internationally (Nyland and Lafferty 2012;Ruhl and Lordly 2017;Morgan et al 2019a). Providing students with experiences across diverse practice contexts to illustrate the breadth of possible careers is one potential strategy.…”
Section: Discussionmentioning
confidence: 89%
“…The flexibility of working in two areas of practice concurrently during placements also provided learning opportunities and personal growth for the students as they needed to learn to adjust. The relevance to student training of real-world modelling of mixed task roles by supervisors observed in this study has also been demonstrated in a systematic review investigating the factors that influence dietetics students’ educational experience and work-readiness [ 31 ]. In the current study, some students were challenged by the need for flexibility and ‘switching of brains’ from patient to a project focus but this also contributed to graduate attribute skills of adaptability.…”
Section: Discussionmentioning
confidence: 71%
“…Participants’ views that graduate preparedness could be enhanced to better match future workforce needs by enabling students to undertake placements in broader, emerging and more contemporary areas of practice, rather than just in traditional ones, echoes calls by academic dietetics educators , dietetics students and other dietetics researchers . In many countries where sourcing appropriate placements have become an increasing challenge and rigid accreditation processes are limiting placement flexibility, fresh approaches to training students are needed .…”
Section: Discussionmentioning
confidence: 99%